Pengembangan Instrumen Pembelajaran Geometri Berbasis Teori Van Hiele Ditinjau Dari Kecerdasan Spasial Siswa - Azwar Anwar; Mestralitiani Saleda Limbong (Mandalika Mathematics and Educations Journal, 2025)
This study aims to develop a suitable and practical geometry learning instrument based on Van Hiele Theory, taking into account students' spatial intelligence levels. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects were eighth-grade junior high school students. The instruments developed were Student Worksheets (LKS) and geometry learning outcome tests. The results of the validity validation by subject matter experts showed that the instruments were declared very feasible with an average score of 4.17, and media experts showed that the instruments were declared feasible with an average score of 3.74. The practicality of the instruments was assessed using a student response questionnaire, which showed a positive response of 77.70% in the very practical category, while teachers showed a result of 76.43% in the very practical category. It can be concluded that the Van Hiele Theory-based geometry learning instrument developed is feasible and practical for use in facilitating the development of students' geometric thinking levels by considering their spatial intelligence profiles.